Binder effect upon the catalytic behavior of PtCoZSM5 washcoated on cordierite monoliths - Boix, Alicia Viviana (2004)
PtCoZSM5 in powder form is an effective catalyst for the selective reduction of NOx with methane. In order to attach a stable film of this powder to a cordierite honeycomb monolith, several approaches were assayed. Either NaZSM5 or CoNaZSM5 were washcoated on the cordierite, and then either Co and Pt or Pt, respectively, was ion exchanged to obtain the desired composition. Another option explored was to washcoat the PtCoZSM5 powder. Al(NO3)3 used as a binder produced undesirable changes in the catalytic behavior due to the formation of non-stoichiometric cobalt aluminate during the calcination of the monolith at 550 °C. The powder performance was matched when PtCoZSM5 was washcoated without binder. Inspection of the monolith after 80 h on stream showed no deterioration.